The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/ajps.2014.513216
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Histological Analysis of Direct Shoot Organogenesis Induced in Flower Buds Cultures of <i>Allium altissimum</i>

Abstract: The present work gives a detailed study of in vitro shoot organogenesis of the ornamental onion A. altissimum Regel from the buds of the middle layer of the inflorescences. The course of morphogenesis was examined by light and scanning electron microscopy. Histological observation revealed that during 3-5 days of culture on the BDS medium supplemented with 2.0 mg•L −1 of BA and 2.0 mg•L − 1 of NAA the epidermal cells of the stamen filament in the area of its fusion with the tepal became competent and dediffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A similar differentiation pathway of receptacle epidermis played a crucial role in initial stages of Allium altissimum Regel shoot development in vitro culture from the immature inflorescences covered with the spathe (Poluboyarova et al, 2014). The ability to regenerate buds and shoots from subepidermal or epidermal layers was observed earlier in histological Begonia studies (Lai et al, 2018).…”
Section: Resultsmentioning
confidence: 69%
“…A similar differentiation pathway of receptacle epidermis played a crucial role in initial stages of Allium altissimum Regel shoot development in vitro culture from the immature inflorescences covered with the spathe (Poluboyarova et al, 2014). The ability to regenerate buds and shoots from subepidermal or epidermal layers was observed earlier in histological Begonia studies (Lai et al, 2018).…”
Section: Resultsmentioning
confidence: 69%
“…Inclusion of TDZ, which has both auxin and cytokinin-like activity (Guo et al 2011), promoted callus induction in C. sativa inflorescences, but yielded low frequency of floral regeneration (Piunno et al 2019). As a result, the current study focused on the proliferation of shoots using the cytokinins mT and BAP, rather than the induction of callus Floral reversion has also been reported to occur via direct organogenesis through the formation of adventitious shoots and meristemoids from the base of the floral organs (Punyarani et al 2013;Poluboyarova et al 2014;Asker 2016). Histological sampling by Punyarani et al (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Floral reversion has also been reported to occur via direct organogenesis through the formation of adventitious shoots and meristemoids from the base of the floral organs (Punyarani et al 2013; Poluboyarova et al 2014; Asker 2016). Histological sampling by Punyarani et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular development which characterizes floral reversion have been differentially described depending on the species studied (Zayed et al 2016). In some species floral reversion occurs from existing meristems (Sen et al 2013) while from others reversion is a result of de novo regeneration (Poluboyarova et al 2014;Zayed et al 2016). The mode of floral reversion has implications in plant biotechnology where early transient gene expression studies have shown the potential to express transgenes in floral tissues (Deguchi et al 2020).…”
Section: Introductionmentioning
confidence: 99%